The Impact of Selected Factors of Utility Motor Vehicles Operation Conditions on the Economy Driving - Holesa, Lukas; Hrudkay, Karol (Communications - Scientific letters of the University of Zilina, 2015)
Article analyzes the specific conditions of operating commercial vehicles and deals with their influence on the operation economy of a selected vehicle category. The article results are the empirically determined factors of the selected conditions that have the strongest (greatest) influence on variability of the average fuel consumption of selected vehicles. These factors are also supported by appropriate calculations. The next part of the article is creating a regression model through which it is possible to measure the impact of the factor changes on an observed variable.